Popular Financial Reporting: Frankfurt 2023 (European journal of volunteering and community-based projects, 2024)
This document, Popular Financial Reporting: Frankfurt 2023, by Nathan Lin and Giorgia Faragi, provides a comprehensive financial and civic overview of Frankfurt am Main. It details the city's governance, economic and demographic landscape, budget allocations, and financial performance. With a population exceeding 790,000, Frankfurt is an international finance hub, hosting institutions like the European Central Bank. In 2023, the city reported revenues of €1 billion and maintained a robust financial position, with assets of €2 billion and a €800 million surplus. The report also emphasizes Frankfurt’s commitments to sustainability, digital services, and social programs. Initiatives include waste neutrality by 2040, renewable energy investments, and expansive social support for diverse communities. This report aims to increase financial transparency, making complex data accessible to residents and encouraging civic engagement.